LITERACY CULTURE AS AN EFFORT TO IMPROVE STUDENTS' INTEREST IN READING AT STATE ELEMENTARY SCHOOL 088 PANYABUNGAN - Juli Avni; Yenni Efrida Lubis; Nur Azizah Zulkifli; Laila Sakinah Siregar; Rika Fitri Adelina; Nurul Hidayah; Rosita Rangkuti (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
This study explores the phenomenon of literacy culture in an effort to increase students' reading interest at SD Negeri 088 Panyabungan. This activity is carried out daily during the first period, where the homeroom teacher brings students who are not yet fluent in reading to a special room to be guided by the teacher to improve their reading skills. The research approach used is descriptive qualitative to collect students' and teachers' experiences in the process of habituating reading. The results show that the routine implementation of literacy culture has a positive effect on students' interest and reading ability, so that students tend to be more confident and more active in school literacy activities. These findings also indicate the need for consistent school environmental support and literacy-based learning strategies to truly form strong reading habits. This study recommends improving reading facilities and integrating literacy culture into daily school activities.